Possible Health Implications and Low Vitamin D Status during Childhood and Adolescence: An Updated Mini Review. (29th July 2009) - Papandreou, Dimitrios; Malindretos, Pavlos; Karabouta, Zacharoula; Rousso, Israel
Abstract : Vitamin D deficiency is common in the developing countries and exists in both childhood and adult life. The great importance of Vitamin D is the moderation of calcium (Ca) and phosphorus (P) homeostasis as well as the absorption of Ca. While insufficiency of vitamin D is a significant contributing factor to risk of rickets in childhood, it is possible that a more marginal deficiency of vitamin D during life span contribute to osteoporosis as well as potentially to the development and various other chronic diseases such as cardiovascular disease, cancer and diabetes. This paper reviews the metabolism, epidemiology, and treatment of vitamin D and calcium insufficiency as well as its relation to various diseases during childhood and adolescence.